Efficacy of the U‐shaped flap technique in preventing reflux after minimally invasive proximal gastrectomy for proximal gastric and esophagogastric junction cancer - Takeshi Omori; Hisashi Hara; Yoshitomo Yanagimoto; Naoki Shinno; Yasunori Masuike; Takashi Kanemura; Hiroshi Wada; Masayoshi Yasui; Masayuki Ohue; Hiroshi Miyata (Annals of Gastroenterological Surgery)
Abstract Background Preventing gastroesophageal reflux after proximal gastrectomy for proximal gastric and esophagogastric junction cancer remains challenging due to the lack of standardized reconstructive techniques. The double flap technique (DFT) in valvuloplastic esophagogastrostomy prevents reflux esophagitis but is less effective in esophagogastric junction cancer because of negative pressure on the inferior mediastinum. We developed the U‐shaped flap technique (UFT) to enhance the anti‐reflux efficacy. Methods This study analyzed data from patients who underwent minimally invasive proximal gastrectomy for proximal gastric and esophagogastric junction cancer between August 2014 and May 2022, using a prospectively maintained database. We compared DFT and UFT for short‐ and long‐term outcomes, focusing on gastroesophageal reflux, using one‐to‐one propensity score matching to control for patient‐related variables. Results Among 217 eligible patients, 205 (100 in DFT, 105 in UFT) completed a 1‐year follow‐up. After propensity score matching, we selected 42 pairs of patients who underwent DFT and UFT. UFT had significantly shorter operative time (p = 0.044), similar blood loss, and similar morbidity. The UFT group had significantly fewer reflux symptoms (0% vs. 14.3%, p = 0.0011) and endoscopic Los Angeles grade B or higher reflux esophagitis (0% vs. 14.3%, p = 0.0011) than the DFT group. In lower mediastinal reconstructions for esophagogastric junction cancer, UFT showed a reduced incidence of reflux esophagitis. Conclusion Our study indicates that the U‐shaped flap technique (UFT) offered significant advantages in reducing postoperative reflux symptoms and endoscopic esophagitis, in a cohort of patients with proximal gastric and esophagogastric junction cancer.